Lung cancer in patients under the age of 40 years - Kozielski, Jerzy; Kaczmarczyk, Grzegorz; Porębska, Irena; Szmygin-Milanowska, Katarzyna; Gołecki, Marcin (Contemporary Oncology/Współczesna Onkologia, 2012)
Aim of the study : In the paper clinical cases of individuals diagnosed with lung cancer below the age of 40 years have been analyzed. Material and methods: The analysis included: sex, age, clinical symptoms found before and at the moment of diagnosis, character of changes visible in radiological imaging, time that passed from the first symptoms to reporting to a doctor and to establishing a diagnosis, type of diagnostic method used in establishing the final diagnosis, histopathologic type of cancer, degree of cancer progression. Results: The results have been compared with a peer group who had been diagnosed 20 years earlier. Currently 7% of patients were diagnosed at the age of 25 or younger, whereas in the previous cohort patients in this age constituted 2%. The predominant pathological type was adenocarcinoma (currently 33%, previously 4%) in contrast to the earlier group in which 57% of patients had small cell lung cancer (57%). The incidence is equally distributed between both sexes, although there is an evident increase in female lung cancer cases. In the majority of patients the clinical presentation is a peripheral mass on chest X-ray. 20% of patients present pleural effusion on diagnosis. Patients reported the following complaints: breathlessness, chest pain, weight loss and fatigue. The majority of cases were diagnosed in advanced stages on the basis of a bronchoscopy acquired specimen. Time course from symptoms to diagnosis tends to be shorter than 20 years ago.